UNESCO's road towards knowledge societies - Leye, Veva (Javnost (Ljubljana), 2007)
Though traditionally perceived as a more liberal international organisation, the United Nations Educational, Scientific and Cultural Organisation (UNESCO) is part and parcel of the "development machine". Inspired by post-structural thinking in development studies and Jessop's (2004) cultural political economyapproach, we examine the organisation's 2005 World Report Towards Knowledge Societies as a text of development construing and constructing particular discourses. First, we introduce the knowledge-based economy discourse and the information society discourse. Then we situate UNESCO's report as an attempt to provide an alternative to the die-hard information society discourse. Next, we argue that through its allegiance to knowledge-based economy reasoning (concerning education and learning; globalisation and development), UNESCO in this report actually endorses and helps to construct the discourse on the information society. The convergence of information society, knowledge-based economy and neo-liberal thinking has very real material consequences because it provides the ideal discursive context for the ICT4D (Information and Communication Technologies for Development) paradigm, the newest development craze which may be little more than a reissue of the old modernisation paradigm.
Keywords: knowledge; znanje; izobraževanje; education; pospeševanje; družbeni razvoj; tehnološki razvoj; informacijska družba; družba znanja; mednarodne organizacije; UNESCO